Longevity, dormancy and germination of Cyanus segetum. (15th September 2017) - Guillemin, J‐P; Bellanger, S; Reibeil, C; Darmency, H
Summary: Cyanus segetum is an iconic, colourful weed in arable fields that provides ecological and societal services. To understand better both the infestation dynamics of C. segetum as an abundant, harmful weed and maintain sustainable populations where it provides beneficial services, we compared information on seed dormancy, seed longevity and germination conditions in two populations. Persistence of seeds buried in the soil was low, with <10% viable after 3 years. Periodic dormancy cycling was observed over the 4 years in the soil, with a maximum of dormant seeds in the spring and a minimum in the autumn; however, 20% of the seeds were non‐dormant all the time. Seeds of C. segetum were positive photosensitive, but light requirement varied among populations. Base water potential for germination was −1 MPa. Base temperature ranged from 1 to 2°C. Optimum temperature for germination was about 10 to 15°C, but the mean thermal time varied greatly between populations, from 80 to 134 day °C. Photoperiod and temperature combinations had no effect on germination percentage, but both reduced the germination rate. Burial deeper than 2 cm greatly reduced germination and seedling emergence strongly decreased at depths >0.5 cm. No seeds buried deeper than 8 cm emerged. Low seed longevity and a wide range of germination conditions could partly explain the rapid disappearance of C. segetum populations after herbicide application began in western Europe. However, yearly sowing in restoration areas does not seem to be essential.